Clinically Significant Anti-E and Anti-Jka Alloantibodies Identified in a 24-year-old Female suspected of Delayed Hemolytic Anemia Requiring Emergency Transfusion - Bhandari, Udaya Prakash; Maharjan, Sabindra; Nepal, Bipin (Grande Medical Journal, 2025)
Delayed hemolytic transfusion reactions (DHTRs) represent significant complications associated with blood transfusion, often resulting from the development of alloantibodies against specific red blood cell (RBC) antigens. We report a case of a 24-year-old female presenting with fever, generalized weakness, icterus of skin, severe anemia and a transfusion history a week before presentation. Immunohematological evaluation using the NEO-IRIS automated platform with Solid Phase Red Cell Adherence (SPRCA) technology identified anti-E and anti-Jka alloantibodies. Due to the unavailability of anti-JKa reagent, only E-antigen negative compatible blood could be provided. The patient showed significant clinical and hematologic improvement after receiving one unit of compatible blood. This case highlights the importance of comprehensive antibody screening, early referral to transfusion medicine specialists involvement, extended RBC phenotype donor registries and improving access to rare antisera are crucial to ensuring timely provision of antigen-negative units and enhancing transfusion safety.